Evidence-based control of canine rabies: a critical review of population density reduction - Morters, Michelle K (Blackwell Publishing Ltd, 2013)
1. Control measures for canine rabies include vaccination and reducing population density through culling or sterilization. 2. Despite the evidence that culling fails to control canine rabies, efforts to reduce canine population density continue in many parts of the world. 3. The rationale for reducing population density is that rabies transmission is density-dependent, with disease incidence increasing directly with host density. This may be based, in part, on an incomplete interpretation of historical field data for wildlife, with important implications for disease control in dog populations. Here, we examine historical and more recent field data, in the context of host ecology and epidemic theory, to understand better the role of density in rabies transmission and the reasons why culling fails to control rabies. 4. We conclude that the relationship between host density, disease incidence and other factors is complex and may differ between species. This highlights the difficulties of interpreting field data and the constraints of extrapolations between species, particularly in terms of control policies. 5. We also propose that the complex interactions between dogs and people may render culling of free-roaming dogs ineffective irrespective of the relationship between host density and disease incidence. 6. We conclude that vaccination is the most effective means to control rabies in all species.